Portfolio Flows into Indonesia: Push or Pull? - Nuryakin, Chaikal (Economics and Finance in Indonesia, 2016)
This paper focuses on the dynamic of the portfolio flows into Indonesia. The result of Structural Vector Autoregression (SVAR) model reveals that push factors is more dominant than pull factors in explaining portfolio flows into Indonesia. Portfolio flows into Indonesia are positively correlated with regionals stock market performance and negatively correlated to the federal funds rate. On the pull factors, domestic risk (the Credit Default Swap spread) is more dominant than domestic return (the BI rate) in explaining the flows. Thus, it is important for authorities to have more focus on domestic risk relative to rate of return in managing portfolio flows. In addition, the negative impact of the lagged Indonesia stock market index to the capital flows indicates a counter cyclical investment behavior of global investors.